Variation in Chemical Constituents of Siyez Wheat (Triticum monococcum L.) in Response to Some Abiotic Stress Factors - Turfan, Nezahat; Sarıyıldız, Temel; Mutlu, Ekrem (Turkish Science and Technology Publishing (TURSTEP), 2019)
Main aim of this study was to determine the effects of different salt contents (75 mM, 150 mM and 225 mM NaCl), heavy metal (0.2 mg/L FeCl3, NiCl2, ZnCl2), lime (2 mg/L CaCO3), drought (50%) and pollution (0.2 mg/L dust of factories) on photosynthetic pigments, malondialdehyde (MDA), hydrogen peroxide (H2O2) levels, the ascorbate peroxidase (APX), catalase (CAT), guaiacol peroxidase (GPOX) and superoxide dismutase (SOD) in Siyez wheat (Triticum monococcum L.). All experiments were carried out under laboratory conditions with 16 hour-day and 8 hour-night photoperiod in an incubator at 23 ± 1Â°C. Results showed that mean chlorophyll-a concentration was highest in the siyez seedlings treated with the pollution, while both mean chlorophyll-b and total chlorophyll concentrations were highest with 75 mM salt application. Mean total carotenoid was, however, highest with the drought treatment and mean relative water content was highest with NiCl2 application. Mean MDA and H2O2 contents were found to be highest in the siyez seedlings treated with 225 mM salt, whereas they were lowest with NiCl2 treatment. Mean proline content was highest with the NiCl2 treatment compared to the lowest concentration in the control siyez seedlings (82 Âµmol/g). Mean APX, CAT and GPOX activities were noted to be highest in the siyez seedlings treated with NiCl2. In general, the siyez seedlings showed high tolerance to the pollution, NiCl2 and drought with having highest photosynthetic pigments, proline, protein content and enzymes activities. Among all treatments, 225 mM NaCl and CaCO3 negatively influenced chemical compounds of the siyez seedling. When all data are taken into consideration, it can be said that higher photosynthetic pigments, proline contents, antioxidant enzymes activities and lower MDA and H2O2 levels play an important role in the resistance of siyez seedlings against abiotic stress conditions.
Keywords: tolerance; antioxidant; S; Agriculture (General); [No Keywords]; Agriculture; abiotic stresses; S1-972; wheat; siyez; 2. Zero hunger; 15. Life on land; 6. Clean water; 13. Climate action